2006
DOI: 10.1111/j.1365-2362.2006.01737.x
|View full text |Cite
|
Sign up to set email alerts
|

ApoA‐I mutants V156K and R173C promote anti‐inflammatory function and antioxidant activities

Abstract: The V156K-rHDL and R173C-rHDL displayed potent beneficial effects, including anti-oxidant and anti-inflammatory activity from both in vitro and in vivo evaluations, whereas the WT-rHDL and A158E-rHDL did not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 30 publications
2
27
0
Order By: Relevance
“…Additionally, this result indicates that artificial sweetener-mediated modification is very similar to the chemical reaction of fructose. ApoA-I is well-known for its antioxidant ability in both lipid-free and lipid-bound states (Cho et al, 2006). Similarly, Liz et al (2007) reported that cleavage of apoA-I (26 kDa) by transthyretin is associated with loss of unique features of dysfunctional HDL and an increase in amyloidogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, this result indicates that artificial sweetener-mediated modification is very similar to the chemical reaction of fructose. ApoA-I is well-known for its antioxidant ability in both lipid-free and lipid-bound states (Cho et al, 2006). Similarly, Liz et al (2007) reported that cleavage of apoA-I (26 kDa) by transthyretin is associated with loss of unique features of dysfunctional HDL and an increase in amyloidogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo test using hypercholesterolemic mice The experimental design of the in vivo test was identical to our previous report (Cho et al, 2006). In brief, normal male C57BL/6J mice (22-24 g of body weight) were obtained at 5-weeks of age from the Jackson Laboratory (Bar Habor, ME).…”
Section: Measurement Of Cholesterol Delivery Into Hepg2 Cellsmentioning
confidence: 99%
“…§ HCHF diet containing 0.5% cholesterol/15% lard/0.1% sodium cholate. ∥ Experimental design and data were adopted from our previous report (Cho et al, 2006) Statistical analysis All data were expressed as the means ± S.D. Data was evaluated via one-way Analysis of Variance (ANOVA) using SPSS, and the differences between the means were assessed via Duncan's multiplerange test.…”
Section: Atherosclerotic Lesion Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Purification of WT and V156K apoA-I WT and V156K apoA-I were expressed in an E. coli expression system and then purified using Ni 2+ -column chromatography as described previously (Cho et al, 2006;Han et al, 2005). Protein purity was assessed by 20% sodium dodecyl sulfate-poly acrylamide gel electrophoresis using a Pharmacia Phast System (Uppsala, Sweden).…”
Section: Methodsmentioning
confidence: 99%